ANALISIS PENDAPATAN DAN PEMASARAN COKELAT PADA INDUTRI â€œSAKAYA COKELATâ€ DI KOTA PALU - Ramlah, Siti; Hadayani, Hadayani (AGROTEKBIS, 2019)
This research aimed to determine the income received by producer, marketing channel model, marketing margin, price part and marketing efficiency of chocolate industry Sakaya coklat in Pengawu village of Palu. The industry was purposively chosen with consideration that it is the one with the lowest chocolate production capacity in Palu. Data collected was analyzed using income and marketing analysis. The results analysis revealed that the income generated during the period of June 2017 was IDR 1,993,112. There were two cacao marketing channels: (a) producer seller retailer consumer and (b) producer consumer. The margin obtained from the marketing channel was IDR 14.000. The price part received by the producer on the marketing channel was 84.2% for a box of 12 chocolates weight 7 g each, 80% for a chocolate pack of 40 g and 50 g. The marketing efficiency of the first and the second channels was 47.13% and 22.93%, respectively.